1981
DOI: 10.1002/jrs.1250100144
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational spectra of ethylene monomer and dimer in argon matrices

Abstract: Raman spectra of ethylene trapped in argon matrices are compared with the corresponding infrared data. Bands due to monomer and dimer species could be distinguished by their concentration dependence. Possible structures of the dimer are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…In the following, to help recognize how the ethylene modes change upon adsorption, we keep the symmetry notation of the isolated ethylene ( D 2 h point group). The vibrational frequencies computed in the gas phase are close to the corresponding experimental values . Upon adsorption, most of the vibrational frequencies are downshifted.…”
Section: Introductionsupporting
confidence: 76%
“…In the following, to help recognize how the ethylene modes change upon adsorption, we keep the symmetry notation of the isolated ethylene ( D 2 h point group). The vibrational frequencies computed in the gas phase are close to the corresponding experimental values . Upon adsorption, most of the vibrational frequencies are downshifted.…”
Section: Introductionsupporting
confidence: 76%
“…Vibrational frequencies for monomer ethylene and for the dimer of orientation K were calculated at the HF/6-311G* level. 33 The calculations show that the shifts of the frequencies and the changes of the intensities are small. The comparison shows that many fundamentals exhibit slight red shifts.…”
Section: Resultsmentioning
confidence: 94%
“…Rytter and Grued2 and Cowieson et al 33 have reported the analysis of IR spectra of ethylene dimer in an Ar matrix. The structure of ethylene dimer is still a controversial issue, as mentioned in the Introduction.…”
Section: Resultsmentioning
confidence: 99%
“…From IR spectra of the etylene dimer in Ar matrix, Rytter et al [35] and Cowieson et al [36] proposed that structure of the etylene dimer has D2a symmetry. This is consistent with the experimental measurement of the dipole moment of the etylene dimer which predicted a nonpolar system [37].…”
Section: Iii3 Etylene Dimermentioning
confidence: 99%